PENGARUH LIMBAH CAIR TEKSTIL TERHADAP KUALITAS AIR DI SUB SUB DAS SEMIN KECAMATAN SUKOHARJO, KABUPATEN SUKOHARJO, JAWA TENGAH - Endah Novianti; Rr. Dina Asrifah (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Langsur's River is a part of watershed Semin, which crosses the industrial area in Sukoharjo. The growing textile industry in Sukoharjo is 7.22% from 2007 to 2018, which wasn't followed by good textile waste management. There are indications of river water pollution with poor turbidity, color, and odors, besides indication of slightly salty groundwater contamination. The purpose of this study determined the distribution of liquid waste and to analyze the effect of textile industrial wastewater on the quality of river water and groundwater. The data collecting method uses survey, mapping, and laboratory tests, while sampling method uses purposive sampling. The analysis method uses Pollution Index. The spreading of textile wastewater in the river follows the river flow and strongly influences water quality to light to moderate pollution. Spreading wastewater in groundwater follows the groundwater flow but doesn't strongly influence groundwater which light polluted. The level of river water and groundwater pollution becomes information for effective and efficient water management directions.